Reading Strategy on Internet for Enhancing Reading Profiency - Agus Rofi’i; Noermanzah Noermanzah (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
This study aim describes an overview of the research related to second language learners and reading strategies. It also considers the more recent research focusing on strategies of reading English texts on internet. The following questions are addressed: (1) what is strategy of reading English text? (2) What is the kind of reading strategy that appropriate for English text on Internet? (3) How is the strategy of reading English text applied on Internet for enhancing reading proficiency? The research method uses qualitative methods. It aims to find out the appropriate strategy in order to enhance reading proficiency. In collecting the data, the writer uses library research. The data analysis process has been carried out by reading the data, reducing, classifying, analyzing, and interpreting. Based on the results of the analysis, there are six strategies for reading proficiency on the internet to improve reading skills, namely predicting, previewing, scanning, skimming, reading for details, and speed reading. From the final result, the writers know the appropriate strategy of reading English text on internet is speed reading.